Influence of microstructure on the cutting behaviour of silicon. (15th February 2016) - Goel, Saurav; Kovalchenko, Andrii; Stukowski, Alexander; Cross, Graham
Abstract: We use molecular dynamics simulation to study the mechanisms of plasticity during cutting of monocrystalline and polycrystalline silicon. Three scenarios are considered: (i) cutting a single crystal silicon workpiece with a single crystal diamond tool, (ii) cutting a polysilicon workpiece with a single crystal diamond tool, and (iii) cutting a single crystal silicon workpiece with a polycrystalline diamond tool. A long-range analytical bond order potential is used in the simulations, providing a more accurate picture of the atomic-scale mechanisms of brittle fracture, ductile plasticity, and structural changes in silicon. The MD simulation results show a unique phenomenon of brittle cracking typically inclined at an angle of 45°–55° to the cut surface, leading to the formation of periodic arrays of nanogrooves in monocrystalline silicon, which is a new insight into previously published results. Furthermore, during cutting, silicon is found to undergo solid-state directional amorphisation without prior Si–I to Si-II (beta tin) transformation, which is in direct contrast to many previously published MD studies on this topic. Our simulations also predict that the propensity for amorphisation is significantly higher in single crystal silicon than in polysilicon, signifying that grain boundaries eases the material removal process. Graphical abstract: